2021
DOI: 10.2106/jbjs.rvw.21.00115
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia in Total Shoulder Arthroplasty

Abstract: » For shoulder arthroplasty, regional anesthesia is safer when compared with general anesthesia. There is insufficient evidence to demonstrate the superiority of regional anesthesia with respect to pulmonary complications and hospital length of stay.» Infiltration of the shoulder with local anesthetics offers no additional benefits compared with single-shot or continuous brachial plexus blocks for shoulder arthroplasty.» There is high-quality evidence (Level I) demonstrating lower pain scores and lower periope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Systematic review found that liposomal bupivacaine was comparable to nonliposomal local anesthetics for TSA [17 ▪▪ ]. Some unblinded data indicate that liposomal bupivacaine reduced pain scores after TSA, compared to interscalene catheters [18].…”
Section: Analgesic Pathway Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic review found that liposomal bupivacaine was comparable to nonliposomal local anesthetics for TSA [17 ▪▪ ]. Some unblinded data indicate that liposomal bupivacaine reduced pain scores after TSA, compared to interscalene catheters [18].…”
Section: Analgesic Pathway Componentsmentioning
confidence: 99%
“…Routine use of perioperative acetaminophen and nonsteroidal anti-inflammatory drugs is recommended [24 ▪▪ ]. Dexamethasone reduces nausea, improves pain control, and decreases opioid use [17 ▪▪ ]. Gabapentinoids such as gabapentin are often included in pathways [4 ▪▪ ].…”
Section: Multimodal Analgesiamentioning
confidence: 99%